2011
DOI: 10.1590/s1806-37132011000400010
|View full text |Cite
|
Sign up to set email alerts
|

Cessação de tabagismo em pacientes de um hospital universitário em Curitiba

Abstract: Objective: To determine the prevalence of smoking and the frequency of smoking cessation counseling among patients at a university hospital, as well as to compare smokers and former smokers in terms of smoking history. Methods:A cross-sectional study involving 629 patients at the Federal University of Paraná Hospital de Clínicas, located in the city of Curitiba, Brazil. Results: Of the 629 patients, 206 (32.7%) were male, 76 (12.1%) were smokers, 179 (28.5%) were former smokers, and 374 (59.5%) were nonsmokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 12 publications
5
9
0
5
Order By: Relevance
“…The prevalence of smoking identified in the present study (15%) was similar to that reported by investigations performed in other general hospitals in the country (4)(5)7,12) . The high number of participants who actively smoked at the time of admission may be attributable to the fact that most subjects in our sample of surgical patients had been admitted for elective procedures.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The prevalence of smoking identified in the present study (15%) was similar to that reported by investigations performed in other general hospitals in the country (4)(5)7,12) . The high number of participants who actively smoked at the time of admission may be attributable to the fact that most subjects in our sample of surgical patients had been admitted for elective procedures.…”
Section: Discussionsupporting
confidence: 90%
“…The sociodemographic and economic characteristics of the sample were similar to those described in other similar studies (4,5,7,(11)(12)(13)(14)(15) . Patients were, on average, 54 years old, and had therefore reached an age at which the comorbidities associated with lifestyle factors often begin to appear.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations